Optimal training load for the hang clean and squat jump in u-21 rugby players - de Villiers, N. (2011)
This study investigated the optimal training load required for peak-power production in two types of exercises, namely an Olympic-type and a ballistic exercise. The hang clean and the squat jump were selected to represent these two types of exercise. It was ascertained whether a change in strength levels and training status will have an effect on the optimal loads for peak-power production of rugby players. In addition, the influence that different playing positions have on power production was also investigated. Fifty-nine under-21 male rugby players (Mean Age 19.3yrs; SD ± 0.7yr) from two rugby academies, performed a maximal-strength test in the hang clean and squat, followed by a power test in the hang clean and squat jump with loads ranging from 30 to 90% of maximal strength (1RM). Testing was conducted in the pre-season phase and repeated during the inseason phase. Peak power for the hang clean was achieved at 90% 1RM in the pre-season and at 80% 1RM during the in-season. Peak power for the squat jump was achieved at 90% 1RM in the pre-season. However, this location of the optimal loading was not significantly higher than that of the other loadings (60, 70 and 80% 1RM). During the in-season, peak power for the squat jump was reached at 90% 1RM. Here again, the optimal-loading location was not significantly higher than that of the other loadings (50, 60, 70 and 80% 1RM). It was concluded that the optimal load for power production is 90% 1RM for the hang clean and 60-90% for the squat jump. It was found that an improvement in strength levels of the subjects affected both peak-power production and the optimal load in both exercises. During the in-season peak power in the hang clean was reached at 80% 1RM, and at 50% 1RM for the squat jump. There were no significant differences in the performances of subjects from different playing positions (forwards versus backline players). In the hang clean, peak-power production seems to be reliant on increased strength and results in peak-power output at high loads. The squat jump, on the other hand, is more reliant on velocity due to its ballistic nature and is possibly better suited to developing power at lighter loadings. Because it produces peak power at a lower percentage load than the hang clean, the squat jump could be more effective in power development for players who are inexperienced in power training. Long-term exercise periodisation in power training can therefore be employed progressively from simpler exercises (e.g., squat jump) using only the legs, to more complex exercises (e.g., Olympic-lifting) that involve the whole body. This study confirmed that the specific requirements of different sport codes should be considered meticulously before selecting and prescribing exercises and loads for power-training programmes.